1990
DOI: 10.1177/088307389000500108
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Brachial Pals in the Eastern Province of Saudi Arabia

Abstract: The clinical features of 57 patients (31 males, 26 females) with congenital brachial palsy seen at the King Fahd Hospital of the University over a 5-year period are described. Delivery was difficult in 32 (56%), 20 (35%) were large babies (birth weight greater than 3,600 g), and 20 deliveries required either forceps or vacuum extraction. The presentation at delivery was vertex in 45, breech in five, and shoulder in four. Associated injuries or features, encountered in 14 cases, were fractures of the clavicle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 7 publications
1
16
0
1
Order By: Relevance
“…51 Thirty-four publications did not meet any of the present inclusion criteria. 11,43,44,46,49,[51][52][53][54][55]57,58,60,62,63,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] Of the remaining 42 articles, 35 met one criterion, and seven articles met two criteria (Tables III and IV). As none of the articles met three or four criteria, the protocol was changed in that a second reviewer evaluated the papers meeting two inclusion criteria.…”
Section: Results Of Searchmentioning
confidence: 99%
“…51 Thirty-four publications did not meet any of the present inclusion criteria. 11,43,44,46,49,[51][52][53][54][55]57,58,60,62,63,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] Of the remaining 42 articles, 35 met one criterion, and seven articles met two criteria (Tables III and IV). As none of the articles met three or four criteria, the protocol was changed in that a second reviewer evaluated the papers meeting two inclusion criteria.…”
Section: Results Of Searchmentioning
confidence: 99%
“…Tracti on to the brachia l plex us or phrenic nerve during diffi cult deliveries or vagi nal bree ch deliverie s may occur , and 75% o f cases of diap hragmati c paralys is caused by birth injury have associa ted brachia l plexus pals y. [15][16][17][18] Craniofacial The head is elon gated into a dolichoc ephalic form, often with a p rominent occip ital shel f. There may be redun dant fol ds of skin in the posterior neck as a resu lt of compres sion due to ret roflexion of the head ( Fig. 42-7 ).…”
Section: Featur Esmentioning
confidence: 99%
“…This can also occur during breech deliveries when the adducted arm is pulled forcefully downward to free the after-coming head, which accounts for 9% to 24% of brachial plexus palsies. [15][16][17] The lower plexus is most susceptible to injury when traction is exerted on an abducted arm, such as occurs during breech deliveries when traction is applied to the trunk or legs while the after-coming arm is fixed in abduction. 14 When traction is particularly rapid and forceful, then diffuse multifocal injury occurs, including avulsion of the roots from the cord in the most severe injuries.…”
Section: Limbsmentioning
confidence: 99%
“…The authors ascribed the reduction to improved obstetric practice (13). Subsequent reports, including two population-based studies from Sweden (10,11), have suggested an increase in the incidence, possibly due to an increase in mean birth weight (10,11,(14)(15)(16). However, the incidence in the United Kingdom and Ireland has not changed in nearly 40 years (17).…”
Section: Incidencementioning
confidence: 99%